2021
DOI: 10.1182/bloodadvances.2020004162
|View full text |Cite
|
Sign up to set email alerts
|

Platelet variability index: a measure of platelet count fluctuations in patients with immune thrombocytopenia

Abstract: Fluctuations in platelet count levels over time may help distinguish immune thrombocytopenia (ITP) from other causes of thrombocytopenia. We derived the platelet variability (PVI) score to capture both the fluctuations in platelet count measurements and the severity of the thrombocytopenia over time. Raw PVI values, ranging from negative (less severe thrombocytopenia and/or low fluctuations) to positive (more severe thrombocytopenia and/or high fluctuations) were converted to an ordinal PVI score, from 0 - 6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…46 Previous studies have shown that a very low platelet count level and variability from one platelet count measurement to the next can help distinguish between ITP from non-immune thrombocytopenia. 25 Maximum MPV reflects a high IPF (percentage of reticulated circulating platelets) and has also been associated with the ITP diagnosis in previous studies. 8,47 We then Abbreviations: CI, confidence interval; ITP, immune thrombocytopenia.…”
Section: Sensitivity Analysesmentioning
confidence: 67%
See 4 more Smart Citations
“…46 Previous studies have shown that a very low platelet count level and variability from one platelet count measurement to the next can help distinguish between ITP from non-immune thrombocytopenia. 25 Maximum MPV reflects a high IPF (percentage of reticulated circulating platelets) and has also been associated with the ITP diagnosis in previous studies. 8,47 We then Abbreviations: CI, confidence interval; ITP, immune thrombocytopenia.…”
Section: Sensitivity Analysesmentioning
confidence: 67%
“…The performance of the tool in patients who previously received treatment compared to treatment‐naïve patients requires further study. Another limitation was that one of the predictors, platelet count variability, required at least three platelet count measurements to provide information on platelet fluctuation 25 . In our study population, 523/919 (56.9%) patients with thrombocytopenia had at least three platelet count measurements within 5 years before initial medical consultation; thus, the model could not be applied to all patients (and this proportion may be different in other clinics).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations